Bedside bronchoscopy in intubated patients with acute exacerbation of COPD requiring invasive mechanical ventilation: clinical applications, procedural timing, and standardized management - Juan He; Yu Yao; Xing Chen; Yanyan Yang; Wen Tao (Frontiers in Medicine, 2026)
Introduction Bedside bronchoscopy is a valuable diagnostic and therapeutic tool for intubated patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) receiving invasive mechanical ventilation, yet evidence-based guidance on procedural timing remains limited. Methods This narrative review synthesized evidence from guidelines, systematic reviews, randomized controlled trials, and clinical studies identified through PubMed, Cochrane Library, and Chinese databases (CNKI, Wanfang) from inception through June 2026. Selection was iterative and based on relevance to the four clinical scenarios examined. Results The available evidence suggests that bedside bronchoscopy may be associated with improved oxygenation, reduced ventilator days, lower VAP rates, and facilitated weaning. We propose a preliminary four-scenario framework for procedural timing: early post-intubation, during mechanical ventilation, pre-extubation (at the proposed pulmonary infection control window), and post-extubation failure. Key aspects of standardized management—including pre-procedural risk assessment, ventilator adjustments, sedation strategies, intraprocedural monitoring, and post-procedural care—are discussed, with special attention to resource constraints in secondary hospital ICUs. Discussion The evidence base remains limited and predominantly derived from small, single-center studies, many with potential risk of bias. This framework is hypothesis-generating and requires prospective validation before informing clinical practice recommendations. Future pragmatic multicenter randomized trials are needed.